Transition Metal and Rare Earth Element Doped Zinc Oxide Nanowires for Optoelectronics - Roeder, Robert; Geburt, Sebastian; Zapf, Maximilian; Franke, Dennis; Lorke, Michael; Frauenheim, Thomas; Da Rosa, Andreia Luisa; Ronning, Carsten (physica status solidi (b), 2019)
Even though intrinsic semiconductor nanowires have already extraordinary optical properties, doping with optically active impurities significantly expands the potpourri of optoelectronic applications, such as for nanowire lasers or single photon emitters. This feature article therefore supplies a snapshot of the most recent progress on the structural and optical properties of transition metal and rare earth element doped zinc oxide (ZnO) nanowires using ion beam doping. Here, ion implantation is advantageous, as concurrent defect generation and diffusion upon subsequent annealing allows the formation of defect complexes. This scenario is in many cases even inevitable for the optical activation of the intra-shell luminescence of the implanted impurities, as density functional theory calculations demonstrate. Finally, this article also provides the optimum preparation conditions for intense optical activity and a review on the specific luminescence properties of various optical centers in ZnO nanowires.
CRIS-Team Scopus Importer:2023-04-20
Keywords: ion implantation; optical active centers; semiconductor nanowires; zinc oxide